Revitalization of Local Wisdom Values as a Medium of Da‘wah in Rural Islamic Communities: A Case Study in Bilebante Village, Central Lombok - Pratama, Yoga Prakusya (ISLAMIKA, 2025)
This study addresses the limited research on the role of local wisdom as a medium of da‘wah, despite its substantial influence on religious and social cohesion in rural communities. Focusing on Bilebante Village, the research explores how practices such as gotong royong (communal cooperation), begibung (communal eating), sangkep (village deliberation), and socio-religious events function as dynamic channels for religious propagation, while also examining how social construction, leadership, and communication strategies enhance their effectiveness. A qualitative research design was employed, involving 20 purposively selected participants, including village leaders, religious figures, and youth volunteers. Data were collected through in-depth interviews, direct observation, and document analysis, and analyzed thematically. The findings indicate that local wisdom practices reinforce solidarity, embed Islamic values in everyday life, and foster participatory da‘wah. Social construction processes—externalization, objectification, internalization, and intergenerational transmission were found to sustain value transmission to younger generations. Local leaders emerged as key change agents, promoting both adoption and innovation, while contextual communication strategies utilizing local language, cultural symbols, and digital media enhanced engagement and effectiveness. The study concludes that culturally grounded da‘wah, supported by social construction and adaptive leadership, strengthens both religious teachings and community cohesion. Theoretically, the research extends the study of rural da‘wah strategies, while practically offering recommendations for religious leaders, educators, and policymakers to integrate cultural practices into religious outreach. Future research directions include comparative multi-village studies, longitudinal analysis of local wisdom adoption, and exploration of digital platforms in da‘wah dissemination.